2021
DOI: 10.24940/ijird/2021/v10/i5/may21005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cactus (Opuntia Ficus Indica) and Prosopis Juliflora-Based Rations on Performance of Red Masai Weaner Lambs in Kenya

Abstract: The purpose of this study was to determine plausible pathways to combat feed scarcity and quality in dry lands using locally available and under-utilized feed resources. Red Maasaiweaner lambs were blocked on the basis of body weight and physiological condition. The treatment diets included pure rations of Cenchrusciliaris hay (control) and proportionally determined combinations of P. juliflorapod meal, spineless (O. ficusindica) Cactus leaf meal and C. ciliaris hay. Analysis of variance (ANOVA) methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Though [25,26] reported higher values of ash for the spineless forms compared to spiny types, the results in the current study showed inconsistent results, in which the top three were of the spineless type and the remaining of both forms. To the contrary, [2,27,28] reported the ash values of spiny cladodes higher than those of spineless cladodes.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Though [25,26] reported higher values of ash for the spineless forms compared to spiny types, the results in the current study showed inconsistent results, in which the top three were of the spineless type and the remaining of both forms. To the contrary, [2,27,28] reported the ash values of spiny cladodes higher than those of spineless cladodes.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Particularly, charcoal made from Prosopis wood has been shown to be profitable at some sites [30,61]. The making of flour for human consumption or of animal feed from pods can contribute to generating income while reducing new invasions by the removal of potentially viable seeds [62,63]. Prosopis can have a positive effect on some soil parameters.…”
Section: Impacts Of Prosopis Invasionmentioning
confidence: 99%
“…Durigan et al [33] highlighted the necessity of prevention and control actions to avoid or reverse negative effects of biological invasions. Similarly, attempts to control the spread of P. juliflora through management by utilization have been undertaken in Ethiopia [34][35][36] and Kenya [37]. However, control through utilization does not work.…”
Section: Introductionmentioning
confidence: 99%